Educação corporativa e subjetividade: um estudo de caso - Silva, Celia Maria Marcondes Ferraz (2007)
The present research work represents an attempt to promote a better understanding of how the college programs developed by some corporations actually exert influences on the people psychics, especially when the employee does not have a solid background, and what is gotten from such programs performs an important part of their education. This thesis aims to a contribution of the significant role of corporate colleges for people s education, as long as they could represent in the future an important share of Brazilian educational effort in general standards. Our basic assumption resides on the fact that when the program is effectively oriented to attend only economic needs, as long as reflects the capitalism ideology, it exerts a significant influence on people s mind, self consciousness, as well as self identity. The discussion starts on the analysis of the psychics upper categories. The human being has consciousness, activity and identity. However, in order to reach those categories, we need to research the language, the thoughts and emotions represented by the link between subjectivity and society. Throughout social relationships people internalize the word and build a sense of subjectivity. Using words, during the social life this subjectivity becomes objective through human behavior. There is a dialectic relationship between subjectivity and objectivity. Education represents an important influence especially to build people s subjectivity. When the work education consists not only of a training focused on professional skills, it enables a person to be shaped so as to fulfill the capitalism needs, however without important communication and relationship skills to live in society